2016
DOI: 10.1016/j.resuscitation.2016.07.237
|View full text |Cite
|
Sign up to set email alerts
|

Practice characteristics of Emergency Department extracorporeal cardiopulmonary resuscitation (eCPR) programs in the United States: The current state of the art of Emergency Department extracorporeal membrane oxygenation (ED ECMO)

Abstract: Purpose To characterize the current scope and practices of centers performing extracorporeal cardiopulmonary resuscitation (eCPR) on the undifferentiated patient with cardiac arrest in the emergency department. Methods We contacted all US centers in January 2016 that had submitted adult eCPR cases to the Extracorporeal Life Support Organization (ELSO) registry and surveyed them, querying for programs that had performed eCPR in the Emergency Department (ED ECMO). Our objective was to characterize the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 40 publications
0
68
1
1
Order By: Relevance
“…While similar descriptive analyses of ECPR process variables and complication rates exist for cardiac arrests of all locations (being comprised of mostly IHCA patients) [16], this is the first ELSO registry-based descriptive analysis of ECPR for strictly OHCA. The vessels cannulated and cannula diameter used from this large international registry-based study are similar to prior reports of such process variables from smaller case series or single regions [815,21]. The observed overall median duration of ECPR of 47 h, with a significantly longer duration in survivors than non-survivors (78 vs 37 h, p < 0.05), is within range of prior widely varying reports of ECPR duration following OHCA (10–156 h [2,3,8,9,12,14,15,19]).…”
Section: Discussionmentioning
confidence: 53%
“…While similar descriptive analyses of ECPR process variables and complication rates exist for cardiac arrests of all locations (being comprised of mostly IHCA patients) [16], this is the first ELSO registry-based descriptive analysis of ECPR for strictly OHCA. The vessels cannulated and cannula diameter used from this large international registry-based study are similar to prior reports of such process variables from smaller case series or single regions [815,21]. The observed overall median duration of ECPR of 47 h, with a significantly longer duration in survivors than non-survivors (78 vs 37 h, p < 0.05), is within range of prior widely varying reports of ECPR duration following OHCA (10–156 h [2,3,8,9,12,14,15,19]).…”
Section: Discussionmentioning
confidence: 53%
“…Intensive care specialists experienced with ECLS cannulation perform percutaneous ECPR cannulation in some centres. A recent survey of US centers that perform emergency room ECLS suggested that 15% of emergency department-based ECLS programs do not utilize cardiothoracic surgeons (51).…”
Section: Ecpr Program Organizationmentioning
confidence: 99%
“…Brought to you by | MIT Libraries Authenticated Download Date | 5/13/18 9:44 AM clusion criteria when selecting a patient for ECPR [16]. Generally, it is recommended that the interdisciplinary team should be activated in order to decide whether or not to initiate ECPR in patients who do not present with any sign of a return of spontaneous circulation (ROSC) after ten minutes of advanced cardiac life support [17].…”
Section: Ecpr-who When and To Whom?mentioning
confidence: 99%